Clopidogrel Monotherapy versus Aspirin Monotherapy in Patients with Established Cardiovascular Disease: Systematic Review and Meta-Analysis - Tasoudis, Panagiotis T.; Kyriakoulis, Ioannis G.; Sagris, Dimitrios; Diener, Hans Christoph; Ntaios, George (Thrombosis and Haemostasis, 2022)
Background There is no clear consensus on whether aspirin offers better outcomes in terms of secondary cardiovascular disease prevention compared with clopidogrel.Objective The aim of the study was to compare the safety and efficacy of clopidogrel versus aspirin in patients with established cardiovascular disease.Methods A systematic review of MEDLINE (via PubMed), Scopus, and Cochrane Library databases (last search date: August 28, 2021) was performed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) statement for randomized control trials (RCTs) of clopidogrel versus aspirin as monotherapy in patients with established cardiovascular disease. Random-effects meta-analyses were performed.Results Five RCTs incorporating 26,855 patients (clopidogrel: 13,426; aspirin: 13,429) were included. No statistically significant difference was observed between clopidogrel and aspirin in terms of all-cause mortality (odds ratio [OR]: 1.01 [95% confidence interval, CI: 0.91–1.13]; p = 0.83), ischemic stroke (OR: 0.87 [95% CI: 0.71–1.06]; p = 0.16), and major bleeding rates (OR: 0.77 [95% CI: 0.56–1.06]; p = 0.11). Patients receiving clopidogrel had borderline lower risk for major adverse cardiovascular events (MACE) (OR: 0.84 [95% CI: 0.71–1.00]; p = 0.05) and lower risk for nonfatal myocardial infarction (OR: 0.83 [95% CI: 0.71–0.97]; p = 0.02, relative risk reduction = 16.9%, absolute risk reduction = 0.5%, number needed to treat = 217 for a mean period of 20 months) compared with patients receiving aspirin.Conclusion In patients with established cardiovascular disease, clopidogrel was associated with a 17% relative-risk reduction for nonfatal MI, borderline decreased risk for MACE, and similar risk for all-cause mortality, stroke, and major bleeding compared with aspirin.Protocol Registration PROSPERO CRD42021283866.
Keywords: clopidogrel; aspirin; monotherapy; cardiovascular disease; efficacy; myocardial infarction; stroke; mortality; safety; major bleeding